BraggNet: integrating Bragg peaks using neural networks. Issue 4 (26th July 2019) - Sullivan, Brendan; Archibald, Rick; Azadmanesh, Jahaun; Vandavasi, Venu Gopal; Langan, Patricia S.; Coates, Leighton; Lynch, Vickie; Langan, Paul
Abstract : It is shown that artificial neural networks can be used to predict the location and shape of neutron Bragg peaks, resulting in increased integration accuracy. Abstract : Neutron crystallography offers enormous potential to complement structures from X‐ray crystallography by clarifying the positions of low‐ Z elements, namely hydrogen. Macromolecular neutron crystallography, however, remains limited, in part owing to the challenge of integrating peak shapes from pulsed‐source experiments. To advance existing software, this article demonstrates the use of machine learning to refine peak locations, predict peak shapes and yield more accurate integrated intensities when applied to whole data sets from a protein crystal. The artificial neural network, based on the U‐Net architecture commonly used for image segmentation, is trained using about 100 000 simulated training peaks derived from strong peaks. After 100 training epochs (a round of training over the whole data set broken into smaller batches), training converges and achieves a Dice coefficient of around 65%, in contrast to just 15% for negative control data sets. Integrating whole peak sets using the neural network yields improved intensity statistics compared with other integration methods, including k ‐nearest neighbours. These results demonstrate, for the first time, that neural networks can learn peak shapes and be used to integrate Bragg peaks. It is expected that integration using neural networks can be further developed to increase the quality of neutron, electron and X‐ray crystallography data.